Recent advances in hybrid metaheuristics for dataclustering - De, Sourav, 1979-; Dey, Sandip, 1977-; Bhattacharyya, Siddhartha, 1975- (The Wiley Series in Intelligent Signal and Data Processing, 2020)
"The book will elaborate on the fundamentals of different meta-heuristics and their application to data clustering. As a result, it will pave the way for designing and developing hybrid meta-heuristics to be applied to data clustering"--